2019
DOI: 10.1016/j.lungcan.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes (PROs) in lung cancer: Experiences from a nationwide feasibility study

Abstract: Our objectives were to examine the feasibility of a nationwide collection of patient-reported outcomes (PROs) in a lung cancer population as well as in various sub-populations, and to describe the characteristics of responders compared to non-responders. Materials and Methods All patients diagnosed with lung cancer in Denmark are registered in the Danish Lung Cancer Registry (DLCR). The 7,295 patients registered in DLCR from 1 October 2013 until 30 September 2015 who had received treatment were eligible. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…We found that lower sociodemographic status was associated with a decreased probability of referral to PRO-based follow-up. This finding is supported by studies regarding questionnaire non-response [8,9]. A Danish study among patients with endometrial cancer found that welleducated patients more often sought medical attendance if symptoms of recurrence occurred than did less educated patients [44].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…We found that lower sociodemographic status was associated with a decreased probability of referral to PRO-based follow-up. This finding is supported by studies regarding questionnaire non-response [8,9]. A Danish study among patients with endometrial cancer found that welleducated patients more often sought medical attendance if symptoms of recurrence occurred than did less educated patients [44].…”
Section: Discussionmentioning
confidence: 77%
“…Age, gender, cohabitation status, education, and co-morbidity were included in the adjusted analyses. The confounder variables were selected a priori based on associations between these factors and questionnaire non-response in previous studies [8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although population-based health experience surveys provide a valuable patient perspective on many aspects of health services, they are prone to selection biases18–20 that might result from missing the experiences of ethnic minorities, people living in the more deprived areas and the youngest and oldest age groups. In addition, there has been a concern that patients with the poorest prognosis are missed, because they are too ill or die before they can complete the survey 20 21. Analysis of early cancer experience surveys in England in 2000 and 2004, for example, showed limited inclusion of lung cancer patients,10 and analysis of CPES data for 2010 raised a concern about the number of patients in the initial sampling frame for some cancer types who died before they could receive they survey 20 21…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there has been a concern that patients with the poorest prognosis are missed, because they are too ill or die before they can complete the survey 20 21. Analysis of early cancer experience surveys in England in 2000 and 2004, for example, showed limited inclusion of lung cancer patients,10 and analysis of CPES data for 2010 raised a concern about the number of patients in the initial sampling frame for some cancer types who died before they could receive they survey 20 21…”
Section: Introductionmentioning
confidence: 99%